1989
DOI: 10.1002/jemt.1060120110
|View full text |Cite
|
Sign up to set email alerts
|

Application of ion‐beam etching techniques to the fine structure of biological specimens as examined with a field emission SEM at low voltage

Abstract: The term "etching," in electron microscopy, refers to the removal of specimen surface layers and includes chemical, electrolytic, and ion-beam methods. The ion-beam etching process is used to remove layers of a target material by bombarding it with ionized gas molecules. Recently, the method has been applied to the field of biological specimens; however, the practical procedures for such organic materials have not been developed. In the present study, we used an apparatus in which a beam of argon ions is colli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Ion beam techniques have long been used for material removal in biological materials to 'etch' away surface layers of the targeted material by bombarding it with ionized gas molecules. This has been utilized to enhance the underlying microstructure for highly detailed structural observations (e.g., Lewis et al, 1968;Kanaya et al, 1982;Yonehara et al, 1989) and also in studies of dentin-adhesive interfaces (e.g., Van Meerbeek et al, 1992;Inokoshi et al, 1993a,b) and dentin restorative systems (e.g, Inokoshi et al, 1993a,b). Most of these studies have employed an ion beam from a gas discharge of an inert gas (typically argon), though more recently, 'focused' ion beams (FIB) that utilize a liquid metal (typically gallium) source (Orloff et al, 2003) to produce a probe of small diameter, now close to 10 nm (Van Es et al, 2004), are increasingly being used in large number of applications such as metrology, inspection, cross sectioning, failure analysis, mask-less micromachining, and preparation of thin foils for TEM (Reyntjens and Puers, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Ion beam techniques have long been used for material removal in biological materials to 'etch' away surface layers of the targeted material by bombarding it with ionized gas molecules. This has been utilized to enhance the underlying microstructure for highly detailed structural observations (e.g., Lewis et al, 1968;Kanaya et al, 1982;Yonehara et al, 1989) and also in studies of dentin-adhesive interfaces (e.g., Van Meerbeek et al, 1992;Inokoshi et al, 1993a,b) and dentin restorative systems (e.g, Inokoshi et al, 1993a,b). Most of these studies have employed an ion beam from a gas discharge of an inert gas (typically argon), though more recently, 'focused' ion beams (FIB) that utilize a liquid metal (typically gallium) source (Orloff et al, 2003) to produce a probe of small diameter, now close to 10 nm (Van Es et al, 2004), are increasingly being used in large number of applications such as metrology, inspection, cross sectioning, failure analysis, mask-less micromachining, and preparation of thin foils for TEM (Reyntjens and Puers, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, the difficulties with interpretation of the results and uncertainty about the side effects of ion manipulation have placed serious limitations on the broad application of ion etching in biology. In spite of this, the results indicated that ions and fast atom sources can reveal the biological structures in a way that cannot be achieved by any other method (Haggis, 1982;Ishitani et al, 1995;Li et al, 2001;Yonehara et al, 1989).…”
Section: Introductionmentioning
confidence: 91%
“…Ion milling is routinely used in many microscopy-related applications, such as transmission electron microscopy (TEM) specimen thinning, surface cleaning for Auger analysis and in secondary ion mass spectroscopy (SIMS). Ion beam techniques have been used for the removal of surface layers from biological material to reveal underlying features (Kanaya et al, 1982(Kanaya et al, , 1992aYonehara et al, 1989). These ,studies generally use an ion beam in the micrometres to millimetres diameter range, extracted from a gas discharge (Brown, 1989), and etch relatively large areas of the specimen.…”
Section: Focused Ion Millingmentioning
confidence: 99%